On Classical Quotient Rings of Skew Armendariz Rings - A. R. Nasr-Isfahani; A. Moussavi (International Journal of Mathematics and Mathematical Sciences)
Let R be a ring, α an automorphism, and δ an α-derivation of R. If the classical quotient ring Q of R exists, then R is weak α-skew Armendariz if and only if Q is weak α˜-skew Armendariz.